Gastroduodenal artery aneurysm/ pseudoaneurysm: a systematic review of reported cases - Lee,Yi-Tzu; Hsu,Chien-Chin; Chen,Kuo-Tai (PeerJ, 2025)
Background This systematic review and meta-analysis investigated the clinical characteristics of patients with gastroduodenal artery aneurysm (GDA), identified risk factors associated with poor clinical outcomes, and elucidated potential differences between various GDA etiologies. Methods A systematic literature search was conducted from January 2000 to October 2023 in the PubMed, EMBASE, and Google Scholar databases. The analysis focused on extracting data regarding clinical presentations, diagnostic modalities, and patient outcomes. Results This meta-analysis included data from 224 patients derived from 207 case reports spanning 47 countries over a 23-year period. The majority of patients presented with comorbidity (85.3%) and had a predisposing factor for GDA (71.9%). The diagnostic accuracy of the three most common diagnostic investigations—namely angiography, abdominal computed tomography, and ultrasound—was 100.0%, 86.2%, and 59.6%, respectively. Transarterial embolization (75.0%) and surgery (24.1%) were the two most common therapeutic approaches. Emergent treatment for GDA was necessary in 31.7% of patients. Notably, hemostasis was achieved after the initial treatment attempt in 82.6% of patients. The in-hospital mortality rate was 6.7%, with complications occurring in 16.1% of cases. A higher percentage of patients with a complicated hospital course were subjected to observation management and presented with shock during hospitalization. Conclusions Patients with GDA often have comorbidities and predisposing factors. Clinical presentations of GDA were found to include abdominal pain, hemorrhage, and obstruction of peripheral structures in the vicinity of the gastroduodenal artery. Splanchnic artery angiography and abdominal computed tomography are recognized as the most accurate tools for diagnosing GDA. Endovascular management is the mainstay treatment approach for most patients and have a high rate of hemostasis success during the initial intervention. Surgical intervention is also a practical treatment. Conservative management with observation management may lead to a complicated hospital course, highlighting the potential benefit of aggressive treatment strategies for GDA. Patients with pancreatitis exhibited more comorbidities, predisposing factors, and a broader spectrum of clinical manifestations compared to those without pancreatitis. However, the in-hospital mortality rate was lower in the pancreatitis group, likely due to the younger age of the patients and the more prominent clinical presentations, which prompted earlier and more extensive diagnostic imaging studies.
Keywords: Gastroduodenal artery; Visceral artery aneurysm; Clinical manifestation; Intervention; Outcome